A Suggested Perception of a Course That Takes into Account the Concepts of Health Awareness and Sport Cultures Among Al-Aqsa University Students - Ahmed Yousef Hamdan (University of Basrah, 2023)
This study aims to identify the proposed vision for a course that takes into account the concepts of health awareness and sport culture among Al-Aqsa University students. The study sample includes (64) male and female physical education lecturers in the Arab world for the year 2021, which were chosen randomly. To achieve this, the researcher prepared a list to identify the topics that must be available in the subject of health awareness and sport culture, consisting of (31) paragraphs. The results of the study conclude that the total degree of the specifications required for the development of health awareness and contemporary sport culture at Al-Aqsa University in the light of academic standards from the point of view of physical education lecturers in the Arab world is large with a relative weight of (75.50%). In addition, the results show that there are no statistically significant differences due to the gender variable. The researcher recommends the necessity of activating the level of sport activities for the purpose of developing and enhancing the concepts of health awareness and sport culture for students according to certain foundations and standards, creating the necessary environment for that, and including some subjects related to health, food and sport awareness among the university's compulsory requirements.